PENGARUH PENGETAHUAN PRODUK DAN PEMASARAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPATU VENTELA PADA TIK-TOK SHOP - Asep Saputra; Taufik Bustami (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This research aims to examine the influence of Product Knowledge and Pemasaran Media Sosial on Purchase Decisions of TikTok Shop products, using a case study of students at Universitas Muhammadiyah Bengkulu. The study involves 110 respondents from Bengkulu City who are active TikTok Shop customers. the results of simple regression analysis show that Product Knowledge significantly affects Purchase Decisions, with a regression coefficient of β = 0.472, t-value = 5.004 > t-table = 1.982, and a significance level of 0.000 < 0.05. Similarly, Social Media Marketing also has a significant effect on Purchase Decisions with β = 0.335, t-value = 3.401 > t-table, and a significance level of 0.001 < 0.05. Multiple linear regression analysis produced the equation Y = 6.574 + 0.472X₁ + 0.335X₂, with an F-value = 52.870 > F-table = 3.08 and a significance level of 0.000, indicating that both independent variables significantly influence Purchase Decisions simultaneously. The coefficient of determination (R²) is 0.495, meaning that 49.5% of the variation in Purchase Decisions can be explained by Product Knowledge and Social Media Marketing, while the remaining 50.5% is influenced by other factors outside the model. In conclusion, both consumer product knowledge and social media marketing strategies play a vital role in enhancing purchase decisions on the TikTok Shop platform. Keywords: Product Knowledge, Social Media Marketings, Purchase Decision